(untitled) (World Science, 2018)
Citrus yield is significantly reduced with the help of various pathogenic fungus. Elsinoe fawcetii Bitancourk De Jenk=Sphaceloma fawcetii Jenk differ by their nature of disseminating and harmfulness.